ANALISIS FAKTOR PENGARUH KEPUTUSAN ASN DALAM MENGELUARKAN ZAKAT PROFESI MELALUI BAZNAS - Al Jihad, Hizbullah; Ekawaty, Marlina (Islamic Economics and finance in Focus, 2024)
According to the BAZNAS Strategic Studies Center, the potential for zakat in Indonesia in 2020 reaches Rp. 327.6 trillion, but the amount of zakat collected in the same year was only around Rp. 12.429 trillion. In this study, Maros Regency was chosen as the research focus because BAZNAS Maros Regency received a total income of Rp. 6,184,383,403 in 2022, with the largest contribution coming from zakat fitrah of Rp. 1,646,818,000, followed by zakat maal (from entities/organizations) of 315,092,717, which came from professional zakat paid by ASN Maros Regency. The purpose of this research is to identify the factors that influence the decisions of ASNs in Maros Regency in issuing professional zakat through BAZNAS in Maros Regency. This study uses a quantitative approach with binary logistic analysis method. The population consists of ASNs in Maros Regency groups 3 and 4 who are Muslim with a sample of 100 respondents. The results showed that the variable knowledge of zakat and service quality had a significant influence on the decisions of ASNs in Maros Regency in issuing professional zakat through BAZNAS in Maros Regency. Meanwhile, the variables of income and trust have no significant effect on the decisions of ASNs in Maros Regency in issuing professional zakat through BAZNAS in Maros Regency. This research is expected to be the basis for BAZNAS in Maros Regency in optimizing the potential for professional zakat among ASNs in Maros.